Formation of nanotubular TiO2 structures with varied surface characteristics for biomaterial applications. Issue 5 (31st January 2018) - Aguirre, Robinson; Echeverry‐Rendón, Mónica; Quintero, David; Castaño, Juan G.; Harmsen, Martin C.; Robledo, Sara; Echeverría E, Félix
Abstract: Nanotubular structures were generated on the surface of titanium c.p. by anodization technique in an aqueous solution of acetic acid (14% v/v) with different sources of fluoride ion (HF, NaF, NH4 F). The aim of using these three different compounds is to study the effect of the counterion (H +, Na + and NH 4 + ) on the morphology, wettability and surface free energy of the modified surface. Nanotubes were generated at 10 and 15 V for each anodizing solution. To further improve surface characteristics, the samples were heat‐treated at 600°C for 4 h and at 560°C for 3 h. SEM images revealed the formation of nanotubes in all anodizing conditions, while their diameter increased proportionally to the electric potential. X‐ray diffraction and micro‐Raman spectroscopy results showed the presence of both anatase and rutile phases, with a higher content of rutile in the coatings obtained using NH4 F and an applied potential of 10 V. The heat‐treatment significantly increased the wettability of the anodic coatings, especially for the coating obtained at 15 V with HF, which showed values < 7 degrees of contact angle. Besides, the nanotubes show a decrease in diameter due to the heat treatment, except for the nanotubes formed in NH4 F. Depending on their surface properties (e.g. low contact angle and high surface free energy), these coatings potentially have great potential in biomedical applications, sensors devices, and catalytic applications among others. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1341–1354, 2018.